Komunikasi Massa Model Dakwah Ramzi: (Analisis Kecamatan Samalanga Kabupaten Bireuen-Aceh) - Ali, Marzuki (Yayasan Madinah Al-Aziziyah, 2024)
This study highlights the importance of utilizing mass media in dakwah, which is no longer limited to delivering sermons from the pulpit but has evolved into a more dynamic and flexible approach in line with the times. The research aims to analyze how the concept of symbolic reality in media influences the delivery of dakwah messages and its relevance in the context of the Transformation of Mass Media Communication in the Dakwah of Teungku Dayah in Samalanga District, Bireuen Regency, Aceh. Data was collected through literature explaining mass communication and interviews related to the transformation of mass media communication in dakwah. The findings of the study reveal two main points. First, understanding symbolic reality in media is crucial for designing compelling and effective dakwah messages. This concept enables the selection of communication models that align with the audience and local environment, thereby enhancing the effectiveness of dakwah in the region. Second, changes in society, technology, and politics influence the power of mass media in spreading dakwah messages. Community conditions, the level of community bonds, and the political situation can affect the role of mass media. Additionally, technological advancements open up new opportunities for using mass media in dakwah. Preachers must be able to adapt their communication strategies to remain effective in disseminating messages and influencing society according to these changes. This research emphasizes the importance of understanding and adapting in dakwah communication through mass media in the context of social and technological transformation.